2013
DOI: 10.1159/000351603
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Inhibits the Hedgehog Pathway Which Is Aberrantly Activated in Acute Promyelocytic Leukemia

Abstract: Background/Aim: Dysregulated Hedgehog (Hh) signaling has been implicated in several human malignancies. Hh signaling inhibitors are predicted to have a minimal effect when the Smoothened receptor is mutated. Implications that Gli proteins are molecular targets of arsenic trioxide (ATO) action prompted us to investigate the expression of Hh signaling in acute promyelocytic leukemia (APL) and the influence of ATO on the Hh signaling pathway in APL. Methods: Quantitative real-time reverse transcription polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
6
23
0
Order By: Relevance
“…We have previously shown, and also demonstrate here, that short and long-term exposure to arsenic activates GLI signaling. However, a number of other groups have argued that arsenic attenuates GLI signaling rather than activates it (Fei et al, 2010;Kim et al, 2010Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). We now show, in agreement with these previous groups, that arsenic can also antagonize GLI/HH signaling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously shown, and also demonstrate here, that short and long-term exposure to arsenic activates GLI signaling. However, a number of other groups have argued that arsenic attenuates GLI signaling rather than activates it (Fei et al, 2010;Kim et al, 2010Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). We now show, in agreement with these previous groups, that arsenic can also antagonize GLI/HH signaling.…”
Section: Discussionsupporting
confidence: 92%
“…We further showed that arsenic exposure levels are positively associated with HH pathway activity in human bladder cancer, a malignancy previously linked to chronic arsenic exposure (Fei et al, 2010). More recently, other reports have shown that arsenic inhibits HH signaling initiated by either HH treatment or high GLI levels, and researchers concluded that arsenic is a functional inhibitor of HH/GLI signaling (Kim et al, 2010(Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). Here, we provide in vitro and in vivo evidence suggesting that arsenic can both activate and inhibit GLI signaling, with the direction of GLI modulation dictated primarily by the starting levels of intrinsic GLI activity.…”
Section: Introductionsupporting
confidence: 51%
“…In contrast, Hedgehog was described to be dispensable in maintenance of AML-LSC. Genetic inactivation of Smoothened in MLL-AF9-transformed LSC did not affect AML development in primary recipient mice (52).…”
Section: Hedgehogmentioning
confidence: 85%
“…However, Hedgehog signaling has been shown to be dispensable for maintenance of normal adult HSCs in conditional knockout mouse models (Table 1; refs. 51,52).…”
Section: Hedgehogmentioning
confidence: 99%
“…These evidences strongly raise the possibility of the application of ATO in teatment of PCa. A few studies have reported that ATO could inhibit tumor cell growth by blocking Hh pathway in rhabdoid tumor, osteosarcoma, Ewing sarcoma, pancreatic cancer stem cells and APL patients [24][25][26][27][28][29]. Furthermore, ATO has been established as a Hh pathway inhibitor [29] and a promising anti-tumor agent for Hedgehog-driven cancers [30].…”
mentioning
confidence: 99%